Development of mathematical model for chip serration frequency in turning of stainless steel 304 using RSM - Amin, A. K. M. Nurul; Sulaiman, Syidatul Akma; Arif, Muammer Din (Trans Tech Publications Ltd., Switzerland, 2012)
Chatter is defined as the self-excited violent relative dynamic motion between the cutting tool and work piece. Chatter is detrimental to all machining operations. In metal turning operations it leads to inferior surface topography, reduced productivity, and shortened tool life. Avoidance of chatter has mostly been through reliance on heuristics such as: limiting material removal rates (to stay within the dynamic stability boundary) or selecting low spindle speeds and shallow depth of cuts. However, the correct understanding of the mechanism of chatter formation in metal cutting reveals that chip morphology and segmentation play a predominant role in chatter formation during machining. Chatter is found to appear as a resonance phenomenon when the frequency of chip serration is equal to or integer multiple of the prominent natural frequency/frequencies of the system component(s). Hence, it is important to study the chip serration frequency. At lower cutting speeds the chip is often discontinuous, while it becomes serrated as the cutting speed is increased. It has been identified that the chip formation process at higher speeds also has a discrete nature, associated with the periodic shearing process of the chip. In this paper a statistical technique is proposed to predict the frequency of chip serration as a function of cutting parameters for two different tool overhang values in turning of stainless steel AISI 304 using Response Surface Methodology (RSM).